Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China. (1st May 2023) - Wei, Jing; Huang, Xiao-Feng; Peng, Yan; Lin, Xiao-Yu; Lei, Zhen-Hua; Cao, Li-Ming; Zhu, Wen-Fei; Guo, Song; He, Ling-Yan
Abstract: The mixing of black carbon (BC) with secondary materials is a major uncertainty source in assessing its radiative forcing. However, current understanding of the formation and evolution of various BC components is limited, particularly in the Pearl River Delta, China. This study measured submicron BC-associated nonrefractory materials and the total submicron nonrefractory materials using a soot particle aerosol mass spectrometer and a high-resolution time-of-flight aerosol mass spectrometer, respectively, at a coastal site in Shenzhen, China. Two distinct atmospheric conditions were also identified to further explore the distinctive evolution of BC-associated components: polluted period (PP) and clean period (CP). Comparing the components of two particles, we found that more-oxidized organic factor (MO-OOA) prefers to form on BC during PP rather CP. The formation of MO-OOA on BC (MO-OOABC ) was affected by both enhanced photochemical processes and nocturnal heterogeneous processes. Enhanced photo-reactivity of BC, photochemistry during the daytime, and heterogeneous reaction at nighttime were potential pathways for MO-OOABC formation during PP. The fresh BC surface was favorable for the formation of MO-OOABC . Our study shows the evolution of BC-associated components under different atmospheric conditions, which should be considered in regional climate models to improve the assessment of the climate effects of BC. Graphical abstract: Image 1 Highlights: More-oxidized organic components were preferentially formed on BC during polluted period. More-oxidized organic components on BC tended to be formed through photochemistry. Aqueous-phase reaction promoted the formation of more-oxidized organic on BC. The surface of fresh BC was favorable for formation of more-oxidized organic components.